2021
DOI: 10.1002/jcla.24201
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycan profiling alterations of serum and immunoglobulin G in immune thrombocytopenia

Abstract: Background The glycosylation alterations of serum and IgG are involved in a variety of autoimmune and inflammatory diseases and have shown great potential in biomarker field. The diagnosis of immune thrombocytopenia (ITP) is exclusive. Our study aimed to discover the potential glyco‐biomarkers for auxiliary diagnosis of ITP. Methods The serum samples were obtained from 61 ITP patients and 35 healthy controls, and IgG samples were purified from 34 out of 61 ITP patients and 35 healthy controls. DNA sequencer‐as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The core fucosylated glycans of IgG Fc fragments, through their association with the Fc gamma receptor IIIa (FcgRIIIa) receptor on NK cells, macrophages, and neutrophils, activate the ADCC pathway, thereby upregulating proinflammatory cytokines and triggering an inflammatory response in the body ( 20 , 33 ). Similar to our findings, a decrease in the level of core fucosylation of IgG N-glycans was discovered in immune thrombocytopenia (ITP) patients, with most patients exhibiting lower levels of core fucosylation being more prone to severe thrombocytopenia ( 58 ). Another study also found a significant reduction in the level of core fucosylation of IgG N-glycans in the blood of multiple sclerosis (MS) patients compared to the control group ( 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…The core fucosylated glycans of IgG Fc fragments, through their association with the Fc gamma receptor IIIa (FcgRIIIa) receptor on NK cells, macrophages, and neutrophils, activate the ADCC pathway, thereby upregulating proinflammatory cytokines and triggering an inflammatory response in the body ( 20 , 33 ). Similar to our findings, a decrease in the level of core fucosylation of IgG N-glycans was discovered in immune thrombocytopenia (ITP) patients, with most patients exhibiting lower levels of core fucosylation being more prone to severe thrombocytopenia ( 58 ). Another study also found a significant reduction in the level of core fucosylation of IgG N-glycans in the blood of multiple sclerosis (MS) patients compared to the control group ( 33 ).…”
Section: Discussionsupporting
confidence: 90%
“…One study reported that IgG N-glycan profiles did not differ between healthy control compared to ITP patients during an acute disease episode [ 127 ]. However, another group reported that IgG N-glycans from acute ITP patients exhibited lower core-fucosylation, which is strongly associated with ADCC promotion [ 81 ]. The Wang et al group reported a decrease in the F(6)A2BG2 N-glycan discriminated between ITP patients and healthy control patients with an AUC of 0.96.…”
Section: Igg N-glycans Altered During Autoimmune and Inflammatory Dis...mentioning
confidence: 99%
“…In these clinical contexts the greatest changes have been observed in galactosylation and sialylation, which in some cases such as in RA correlate with disease activity (155,156). Fc core fucosylation has been observed to be modulated in only few autoimmune diseases, with an increase observed in RA, juvenile idiopathic arthritis and Crohn's diseases and a decrease in SLE, MS, and Lambert-Eaton myasthenic syndrome, immune thrombocytopenia (ITP) and either increase or decrease in different thyroid autoimmune diseases (157)(158)(159). It is worth noting that in this context, total IgGs rather than antigen-specific IgG have generally been analyzed.…”
Section: Igg1 Fc Core Fucosylation In Autoimmune and Inflammatory Dis...mentioning
confidence: 99%